The Glypican-1/HGF/C-Met and Glypican-1/VEGF/VEGFR2 Ternary Complexes Regulate Hair Follicle Angiogenesis - Colin-Pierre, Charlie; Berthélémy, Nicolas; Belloy, Nicolas; Danoux, Louis; Bardey, Vincent; Rivet, Romain; Mine, Solène; Jeanmaire, Christine; Maquart, François-Xavier; Ramont, Laurent; Brézillon, Stéphane (Frontiers in Cell and Developmental Biology, 2021)
The hair renewal involves changes in the morphology of the hair follicle and its micro-vascularization. In alopecia, the hair cycle is accelerated, resulting in the formation of thinner and shorter hair. In addition, alopecia is associated with a decrease in the micro-vascularization of the hair follicles. In this study, the role of glypicans (GPCs) was analyzed in the regulation of the angiogenesis of human dermal microvascular endothelial cells (HDMEC). The analysis of glypican gene expression showed that GPC1 is the major glypican expressed by human keratinocytes of outer root sheath (KORS), human hair follicle dermal papilla cells (HHFDPC) and HDMEC. KORS were demonstrated to secrete VEGF and HGF. The HDMEC pseudotube formation was induced by KORS conditioned media (KORSCM). It was totally abrogated after GPC1 siRNA transfection of HDMEC. Moreover, when cleaved by phospholipase C (PLC), GPC1 promotes the proliferation of HDMEC. Finally, GPC1 was shown to interact directly with VEGFR2 or c-Met to regulate angiogenesis induced by the activation of these receptors. Altogether, these results showed that GPC1 is a key regulator of microvascular endothelial cell angiogenesis induced by VEGF and HGF secreted by KORS. Thus, GPC1 might constitute an interesting target to tackle alopecia in dermatology research.